1991
DOI: 10.1111/j.1365-2958.1991.tb02124.x
|View full text |Cite
|
Sign up to set email alerts
|

Segment IV of a Salmonella flagellin gene specifies flagellar antigen epitopes

Abstract: Each of the two mutants isolated from a fliC (= hag, flagellin-deficient) Escherichia coli strain made motile by a plasmid carrying the fliC gene of Salmonella muenchen by selection for motility in the presence of anti-d (Salmonella flagellar antigen) serum had both lost and gained one or more subfactors of the wild-type antigen. In one mutant codon 246 was GAC (alanine) instead of GCC (asparagine); the other had a deletion of 105 base pairs, explicable by a 10bp direct repeat, starting at bases 782 and 887. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
2

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 20 publications
1
30
0
2
Order By: Relevance
“…There is no obvious correlation between flagellin type and the source of isolation, and we have not observed switching between isotypes within the same strain. 1 Flagellin molecules from diverse bacterial species are commonly observed to share amino acid sequence similarity at their amino and carboxy termini, whereas the central regions are often heterogeneous and contain specific antigenic epitopes (33,43). It is interesting that the first 31 residues of the B. bronchiseptica BB7865 flagellin are as related to the S. typhimurium sequence (80% identity) as the S. typhimunum flagellin is to that encoded by E. coli.…”
Section: Methodsmentioning
confidence: 99%
“…There is no obvious correlation between flagellin type and the source of isolation, and we have not observed switching between isotypes within the same strain. 1 Flagellin molecules from diverse bacterial species are commonly observed to share amino acid sequence similarity at their amino and carboxy termini, whereas the central regions are often heterogeneous and contain specific antigenic epitopes (33,43). It is interesting that the first 31 residues of the B. bronchiseptica BB7865 flagellin are as related to the S. typhimurium sequence (80% identity) as the S. typhimunum flagellin is to that encoded by E. coli.…”
Section: Methodsmentioning
confidence: 99%
“…The central domain (D3) of adjacent subunits in a filament is not connected to each other. This D3 domain corresponds with the hypervariable region located on the surface of the flagellin filament, and there are several lines of evidence showing that the exposed D3 domain contains the major epitopes of H antigen (51)(52)(53)(54). The sequence analysis of P. avenae flagellin genes showed that all of the amino acid residues (14 amino acid residues) varying between the incompatible N1141 and the compatible H8301 strains are located in the D3 domains.…”
Section: Discussionmentioning
confidence: 99%
“…The amino-and carboxy-terminal sequences (regions I and II and region VIII, respectively) are conserved and are thought to be important for polymerization and transportation. The central region, which comprises regions IV, V, and VI, is highly variable in both sequence and length between flagellar antigen genes and is generally believed to determine the epitope of the H antigen (13,18).…”
mentioning
confidence: 99%